LAZER, FORMAÇÃO PROFISSIONAL E CONSTRUÇÃO DE SABERES: um estudo com agentes sociais do Programa Esporte e Lazer da cidade de Sete Lagoas-MG - Maria Aparecida Dias Venâncio (2020)
The City Sports and Leisure Program (PELC) was created by the now extinct Ministry of Sports (ME), with the objective of democratizing access to practices and knowledge about sports and leisure. It develops its actions, through agreements with states, city halls and federal educational institutions and has the training system as its central axis. The purpose of the training was to qualify the execution, through the continuous training of the social agents involved, as they are protagonists in the elaboration and execution of the PELC actions. This way, the objective of the research was to describe and analyze the professional profile and the construction of knowledge about leisure for social agents of the PELC - Agreement of the municipality of Sete Lagoas / MG, considering the supports and influences of people, institutions and groups in the formation of these subjects, as well as understand how this knowledge is articulated in the context of the Program. I combined bibliographic and field study procedures, mobilizing them to understand the themes incorporated in the study problem. In the field, I used data collection techniques and in-person semi-structured interviews. I conducted the study of the professional profile of social agents, for the characterization of the subjects and the selection of the agreement of the municipality of Sete Lagoas for the case study. I used content analysis to apprehend the captured information, which allowed to identify that the experiences of the researched social agents, lived in their trajectories, reflect in their ways of being and acting, favoring the construction and reconstruction of their knowledge and the own intervention experience. Social agents recognize the knowledge necessary to work at PELC and point out that they are acquired through initial or continuing education, through free courses or from the cultural practices they develop, in PELC training and professional experiences. The cultural formation of these subjects is constituted through activities linked to different languages and cultural manifestations and in different contexts such as leisure, work and family, being sources of knowledge construction. Many of these knowledges are demanded, improved and mobilized in the interventions in the PELC and others are identified as missing, and that need to be acquired, for a performance connected with the PELC guidelines and with reality. I understood that the construction of knowledge about the leisure of social agents is a constant and non-linear process, characterized by social, academic and everyday interaction, based on the experiences acquired in their life stories and professional trajectory. They are knowledge related to playing, playing sports, training, the right to leisure, strategies, methodologies, which must be contextualized and consider the participating subjects. Therefore, it is knowledge that influences the way these professionals relate to society, work, leisure, that is, the ways of seeing; of being and relating to the world.